Please tell me how sustainable you are, and I'll tell you how much I value you! The impact of young consumers' motivations on luxury fashion - Amélia Brand\~ao; Francisca Magalh\~aes (Cogent Business & Management, 2023)
This research aims to understand the impact of young consumers' luxury motivations on their attitude towards sustainable luxury (ATSL) and the consequent impact on consumer-based brand equity (CBBE). A cross-cultural quantitative study was conducted to achieve this, and a theoretical model was analyzed through a structural equation model procedure using the partial least squares approach. The results confirm the positive impact of most luxury consumption motivations on a favorable ATSL fashion, showing that sustainability and intrinsic experiential value are the antecedents that most predict young consumers' ATSL. Additionally, a favorable ATSL positively influences CBBE through each block. Further, a moderation analysis showed that the relationship between ATSL and two CBBE blocks (i.e. brand building block (BBB) and brand understanding block (BUB)) is positively affected by the level of luxuriousness associated with a brand. Our findings provide crucial insights for scholars and practitioners when adapting their sustainable branding strategies to this new and disruptive consumer segment to maximize their equity.
Keywords: 650; attitude; consumer-based brand equity; fashion; luxury motivations; sustainability; young consumers